Method for preparing efficient trans-perovskite cell based on buried interface stress release and cell device

By introducing trianylamine derivative molecules as interface buffer layer at the interface between the hole transport layer and the perovskite solar cell, the problem of buried interface stress accumulation in perovskite batteries is solved, and efficient and stable Perovskite solar cell devices.

CN119451516AActive Publication Date: 2025-02-14SHAANXI NORMAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411567945.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The accumulation of buried interface stress in perovskite solar cells due to the mismatch of perovskite and substrate thermal expansion coefficients, affecting device stability and efficiency.

Method used

Trianiline derivative molecules (TAPCs) are introduced as interface buffer layer at the interface between the hole transport layer and the perovskite of perovskite battery. Through its multi-rigid structure and specific molecular structure, it coordinates with Pb2+ to reduce the accumulation of interface stress and Optimize energy level arrangement.

Benefits of technology

It effectively reduces the residual stress in the perovskite film, improves the film's stability and photoelectric conversion efficiency, and enhances the long-term stability of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451516A_ABST
    Figure CN119451516A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solar cells, in particular to a method for preparing an efficient trans-perovskite cell based on buried interface stress release and a cell device, and the cell device structurally comprises an FTO substrate, a NiOx hole transport layer, an SAM hole transport layer, an interface buffer layer, a perovskite absorption layer, a PCBM electron transport layer, a BCP barrier layer and a silver electrode in sequence from bottom to top. According to the invention, the interface buffer agent is integrated to the buried interface of the perovskite layer, and the interface buffer agent has a symmetrical molecular structure and a unique active site (C-N), so that the formation of an iodine vacancy defect is significantly inhibited through differential coordination with Pb < 2 + >, thereby effectively promoting the extraction and transfer of holes, and improving the performance of the perovskite solar cell. Therefore, the buried interface stress in the inverted perovskite solar cells (PSCs) is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to a method for preparing a high-efficiency inverse perovskite cell based on buried interface stress release and a cell device. Background Art

[0002] Perovskite has many advantages such as high extinction coefficient, high carrier mobility, low exciton binding energy and easy solution preparation. The current certified efficiency of formal perovskite solar cells has reached 26.3%, and the certified efficiency of trans cells has also exceeded 26.7%.

[0003] In perovskite cell devices, the stability of the perovskite film often determines the stability of the entire device. At present, all perovskite films need to undergo an annealing step. During this process, due to the mismatch in thermal expansion coefficients between the perovskite and the substrate, unfavorable structural deformation and residual stress often occur at the buried interface between the perovskite and the substrate. This residual stress accelerates the degradation of the perovskite film, destroys the stability of the device, and is one of the important factors hindering the commercialization of perovskite solar cells.

[0004] Therefore, finding a perovskite buried interface stress release process with simple preparation process and low cost is still one of the important topics in achieving efficient and stable perovskite solar cell preparation. Summary of the invention

[0005] In view of the problem in the prior art that residual stress in perovskite cells affects device stability, the present invention provides a method for preparing a high-efficiency inverse perovskite cell based on buried interface stress release and a cell device.

[0006] The present invention is achieved through the following technical solutions: A method for preparing high-efficiency inverse perovskite cells based on buried interface stress release, Step 1, cleaning the FTO glass substrate to obtain a pretreated FTO glass substrate; Step 2, spin coating a nickel oxide nanoparticle aqueous dispersion on the surface of the pretreated FTO glass substrate, and then performing a first annealing treatment to obtain a primary product having a nickel oxide hole transport layer; Step 3, dispersing the SAM powder into an isopropanol solution to prepare a SAM isopropanol mixed solution, and then spin-coating the SAM isopropanol mixed solution onto the surface of the nickel oxide hole transport layer of the primary product, and then performing a second annealing treatment to obtain a secondary product having a SAM hole transport layer; Step 4, spin coating the triphenylamine derivative molecular solution onto the surface of the SAM hole transport layer of the secondary product, and then performing a third annealing treatment to obtain a tertiary product with an interface buffer layer; Step 5, spin-coating the perovskite precursor solution onto the surface of the interface buffer layer of the tertiary product to obtain a quaternary product having a perovskite light absorption layer; Step 6, at room temperature, spin-coating a PCBM chlorobenzene solution on the perovskite film of the fourth product to form a fifth product having a PCBM electron transport layer; Step 7, preparing a BCP barrier layer on the PCBM electron transport layer of the fifth product to form a sixth product having a BCP barrier layer; Step 8, evaporating a silver electrode on the BCP barrier layer of the sixth product to obtain a perovskite battery device.

[0007] Preferably, in step 1, the FTO glass substrate is made of fluorine-doped SnO 2 Transparent conductive glass; during cleaning, the FTO glass substrate is ultrasonically cleaned using acetone solution, isopropanol solution, ethanol solution and ultrapure water in sequence, then blown dry, and finally subjected to ultraviolet ozone treatment to obtain a pretreated FTO glass substrate.

[0008] Preferably, in step 2, the nickel oxide nanoparticles / water in the nickel oxide nanoparticle aqueous dispersion is 0.5-1 mg / mL, the spin coating speed is 3000r-5000r / 30s, and the spin coating thickness is 10-40nm; during the first annealing treatment, the temperature is 100-150°C and the time is 30-60min.

[0009] Preferably, in step 3, the concentration of the SAM isopropanol mixed solution is 0.5-1.5 mg / mL, and the spin coating speed is 2000r~4000r / 30s; during the second annealing treatment, the temperature is 100~150°C and the time is 5~25min.

[0010] Preferably, in step 4, the preparation of the triphenylamine derivative molecular solution is as follows: dissolving the triphenylamine derivative molecular powder in a chlorobenzene solution to obtain a triphenylamine derivative molecular solution with a concentration of 0.5-1.5 mg / mL; wherein the structural formula of the triphenylamine derivative molecule is:

[0011] During the third annealing treatment, the temperature is 100~150 ℃ and the time is 5~25min.

[0012] Preferably, in step 5, the perovskite precursor solution is prepared by mixing PbI with a solute molar ratio of 1:0.98:0.02. 2 :CH(NH 2 ) 2 I: CsI was dissolved in a mixed solvent of DMSO:DMF at a ratio of 1:4 to obtain a perovskite precursor solution; During spin coating, the volume of the added perovskite solution and the area of ​​the perovskite film are related to 9.6~11 μL / cm 2 ; The thickness of the perovskite light absorption layer is 700~800nm.

[0013] Preferably, in step 6, during spin coating, the volume of the electron transport layer solution added is related to the area of ​​the perovskite film by 8-9.6 μL / cm 2 .

[0014] Preferably, in step 7, the solvent of the BCP solution is isopropanol, and during spin coating, the thickness of the BCP barrier layer is 3 to 8 nm; during vacuum thermal evaporation, the thickness of the BCP barrier layer is 5 to 15 nm.

[0015] Preferably, in step 8, a silver electrode with a thickness of 80-100 nm is deposited by thermal evaporation.

[0016] A perovskite solar cell device obtained according to the method for preparing a high-efficiency inverted perovskite cell based on buried interface stress release, characterized in that its structure is, from bottom to top, FTO substrate, NiO x Hole transport layer, SAM hole transport layer, interface buffer layer, perovskite absorption layer, PCBM electron transport layer, BCP blocking layer and silver electrode.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a method for preparing a high-efficiency inverted perovskite cell based on buried interface stress release, which reduces stress accumulation at the buried interface in the inverted perovskite solar cell by introducing a triphenylamine derivative molecule (TAPC) with a multi-rigid structure at the interface between the hole transport layer and the perovskite, aiming to relieve stress accumulation at the buried interface, enhance hole extraction capability, and optimize energy level arrangement.

[0018] Among them, the triphenylamine derivative buffer layer is introduced into the buried interface of the perovskite layer. Specifically, the multiple rigid structures in the 4,4'-cyclohexylbis[N, N-bis(p-phenylaniline)aniline] (TAPC) molecule effectively constrain the expansion and contraction of the lattice and reduce the stress accumulation at the interface. Secondly, it has a symmetrical molecular structure and a unique active site (CN). 2+The coordination of iodine vacancy defects significantly inhibits the formation of iodine vacancy defects, thereby effectively promoting the extraction and transfer of holes. In addition, due to its enhanced compatibility, TAPC can well regulate the energy level arrangement between the hole transport layer and the perovskite. Based on these advantages, low-stress, high-quality perovskite films can be prepared, which are characterized by reduced charge transfer barriers and suppressed non-radiative recombination processes, emphasizing the importance of buried interface residual stress release for the realization of efficient and stable inverted perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A flow chart of a method for preparing a high-efficiency inverse perovskite battery based on buried interface stress release according to the present invention; Figure 2 is the structural formula of the triphenylamine derivative molecule in the present invention; Figure 3 PbI is added to the TAPC prepared in Example 1 of the present invention. 2 Infrared spectrum of the mixed perovskite and TAPC and XPS test comparison chart; Figure 4 A comparison diagram of the (100) crystal plane diffraction peak shift of the upper and lower surfaces of the X-ray diffraction (XRD) of the perovskite film prepared in Example 1 of the present invention and the perovskite film with a buffer layer added; Figure 5 This is a SEM comparison image of the buried interface between the perovskite film prepared in Example 1 of the present invention and the perovskite film with a buffer layer added; Figure 6 This is a SEM comparison image of the upper surface of the perovskite film prepared in Example 1 of the present invention and the perovskite film with a buffer layer added; Figure 7 This is a steady-state fluorescence comparison diagram at the lower interface of the perovskite film prepared in Example 1 of the present invention and the perovskite film with a buffer layer added; Figure 8 This is a GIXRD comparison diagram of the upper surface of the perovskite film prepared in Example 1 of the present invention and the perovskite film with a buffer layer added.

[0020] Fig. 9 A comparison chart of the photoelectric conversion efficiency of the perovskite film prepared in Example 1 of the present invention and the perovskite film with a buffer layer added; Fig.10 A comparison chart of the photoelectric conversion efficiency of the perovskite film prepared in Example 2 of the present invention and the perovskite film with a buffer layer added; Fig.11 This is a comparison chart of the photoelectric conversion efficiency of the perovskite film prepared in Example 3 of the present invention and the perovskite film with a buffer layer added. DETAILED DESCRIPTION

[0021] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0022] The present invention discloses a method for preparing a high-efficiency inverse perovskite battery based on buried bottom interface stress release, referring to Figure 1 , including the following steps: Step 1, cleaning the FTO glass substrate to obtain a pre-treated FTO glass substrate; wherein the FTO glass substrate is made of fluorine-doped SnO 2 Transparent conductive glass; during cleaning, the FTO glass substrate was ultrasonically cleaned with acetone solution, isopropanol solution, ethanol solution and ultrapure water in turn, and the cleaning time for each time was 30 minutes. Then, it was blown dry for 1-3 minutes at room temperature (25°C) using a box-type oil-free reciprocating piston air compressor, and finally, ultraviolet ozone treatment was performed to obtain a pretreated FTO glass substrate.

[0023] Step 2, spin coating a nickel oxide nanoparticle aqueous dispersion on the surface of a pretreated FTO glass substrate, and then performing a first annealing treatment to obtain a primary product having a nickel oxide hole transport layer; wherein the nickel oxide nanoparticle / water in the nickel oxide nanoparticle aqueous dispersion is 0.5-1 mg / mL, the spin coating speed is 3000r-5000r / 30s, and the spin coating thickness is 10-40nm; during the first annealing treatment, the temperature is 100-150°C and the time is 30-60min.

[0024] Step 3, dispersing the SAM powder into an isopropanol solution to prepare a SAM isopropanol mixed solution with a concentration of 0.5-1.5 mg / mL, and then spin-coating the SAM isopropanol mixed solution onto the surface of the nickel oxide hole transport layer of the primary product at a spin coating speed of 2000r~4000r / 30s, and then performing a second annealing treatment to obtain a secondary product with a SAM hole transport layer; wherein, during the second annealing treatment, the temperature is 100~150°C and the time is 5~25min.

[0025] Step 4, spin-coating the triphenylamine derivative molecular solution onto the surface of the SAM hole transport layer of the secondary product, and then performing a third annealing treatment to obtain a tertiary product with an interface buffer layer; wherein the triphenylamine derivative molecular solution is prepared by: dissolving the triphenylamine derivative molecular powder in a chlorobenzene solution to obtain a triphenylamine derivative molecular solution with a concentration of 0.5-1.5 mg / mL; wherein the structural formula of the triphenylamine derivative molecule is:

[0026] During the third annealing treatment, the temperature is 100~150 ℃ and the time is 5~25min.

[0027] Step 5, spin-coating the perovskite precursor solution onto the surface of the interface buffer layer of the tertiary product to obtain a quaternary product having a perovskite light absorption layer; wherein the perovskite precursor solution is prepared by: mixing PbI with a solute molar ratio of 1:0.98:0.02 2 :CH(NH 2 ) 2 I: CsI was dissolved in a 1:4 mixed solvent of DMSO:DMF to obtain a perovskite precursor solution. During spin coating, the volume of the added perovskite solution was related to the perovskite film area by 9.6-11 μL / cm 2 ; The thickness of the perovskite light absorption layer is 700~800nm.

[0028] Step 6: At room temperature, spin-coat the PCBM chlorobenzene solution on the perovskite film of the quaternary product to form a quintuple product with a PCBM electron transport layer; wherein, during spin coating, the volume of the electron transport layer solution added is related to the area of ​​the perovskite film by 8-9.6 μL / cm 2 .

[0029] Step 7, preparing a BCP barrier layer on the PCBM electron transport layer of the fifth product by spin coating a BCP solution or vacuum thermal evaporation to form a sixth product having a BCP barrier layer; wherein the solvent of the BCP solution is isopropanol, and when spin coating, the thickness of the BCP barrier layer is 3~8nm; when vacuum thermal evaporation is performed, the thickness of the BCP barrier layer is 5~15nm.

[0030] Step 8, using thermal evaporation to deposit a 80-100 nm thick silver electrode on the BCP barrier layer of the sixth product to obtain a perovskite battery device.

[0031] The present invention dissolves triphenylamine derivative molecules (CAS No. 58473-78-2, produced by Xi'an Yuri Solar Energy Technology Co., Ltd., formerly Xi'an Baolait Optoelectronics Technology Co., Ltd.) in organic solvents such as chlorobenzene, shakes and evenly distributes them for 5 to 8 hours, and then spin-coats them on the prepared SAM hole transport layer and anneals them at high temperature. The specific structure is FTO / NiOx / SAM / triphenylamine derivative molecules (structural formula as shown in Figure 2 As shown in Figure 2). Since the triphenylamine derivative molecules have multiple rigid molecular groups containing benzene rings, these groups contain CN bonds that can be well anchored to the buried interface of the perovskite, thereby limiting the lattice expansion and contraction of the perovskite film during annealing and cooling, thereby constructing a buried interface without residual stress accumulation, while promoting orderly crystallization of the buried interface to improve film growth quality and device stability. In addition, since CN can chelate unpaired Pb 2+ It is captured at the interface, thereby limiting the Pb 2+ The diffusion of ions improves the long-term stability of the device.

[0032] The present invention also provides a perovskite solar cell device obtained according to the method for preparing a high-efficiency inverted perovskite cell based on buried interface stress release, characterized in that its structure is, from bottom to top, FTO substrate, NiO x Hole transport layer, SAM hole transport layer, interface buffer layer, perovskite absorption layer, PCBM electron transport layer, BCP blocking layer and silver electrode.

[0033] Example 1 Step 1, cleaning FTO glass substrate: select fluorine-doped SnO 2 (FTO) transparent conductive glass (2.5*2.5 cm 2 ), wipe off the impurities on the surface with dust-free paper, then use acetone, isopropanol, ethanol and ultrapure water for ultrasonic cleaning for 30 minutes each, blow dry, and treat with ultraviolet ozone for standby use; Step 2, preparing nickel oxide nanoparticle aqueous dispersion: Firstly, a nickel oxide nanoparticle aqueous dispersion is prepared and ultrasonically dispersed; After spin coating and annealing the aqueous dispersion of nickel oxide nanoparticles, a nickel oxide hole transport layer is obtained; Step 3, prepare SAM solution: First, prepare SAM dispersion and disperse by ultrasonication; After spin coating and annealing of the SAM dispersion, a SAM hole transport layer is obtained; Step 4: Prepare the interface buffer layer: After the annealed SAM substrate is cooled to room temperature, the buffer layer molecules are spin-coated or evaporated on the SAM substrate, followed by annealing.

[0034] Step 5, preparing a perovskite light absorption layer; Weigh PbI 2 :CH(NH 2 ) 2 I: Three solutes of CsI are dissolved in a DMSO / DMF mixed solvent; the mixed solution is sealed, stirred sufficiently, and filtered to obtain a clear perovskite solution for use; The perovskite precursor solution is uniformly coated on the surface of the interface buffer layer substrate; the perovskite wet film is obtained by spin coating and then placed on a 110° C. hot plate for 20 minutes to obtain a perovskite light absorption layer; Step 6: Preparation of PCBM transport layer: The annealed perovskite film was cooled to room temperature, and the PCBM solution was spin-coated on the perovskite substrate to obtain the electron transport layer.

[0035] Step 7, preparation of BCP barrier layer.

[0036] The BCP solution is spin-coated on the surface of the PCBM layer or a 5 nm BCP layer is vacuum-evaporated on the surface of the PCBM.

[0037] Step 8, silver electrode evaporation: The prepared film was transferred into the evaporation chamber and 80 nm thick silver electrode was deposited by thermal evaporation. The effective area of ​​the mask plate was 0.09 cm 2 .

[0038] Reference Figure 3 , PbI 2 When added to TAPC solution, infrared spectroscopy revealed that PbI 2 After that, the CN bond in the TAPC molecule was significantly displaced. Then, the triphenylamine derivative molecule was spin-coated on the surface of the perovskite. XPS test showed that the Pb in the perovskite 2+ The above results show that the CN bond in the triphenylamine derivative molecule can anchor the under-coordinated Pb in the perovskite. 2+ , thereby improving the long-term stability of perovskite devices.

[0039] Reference Figure 4 , which reflects the release of residual stress at the buried interface by introducing an interface buffer layer (triphenylamine derivative molecule) between the hole transport layer and the perovskite. By spin-coating the hole transport layer, interface buffer layer and perovskite layer on a glass substrate, we found that there was a large displacement difference between the (100) crystal plane diffraction peaks on the upper surface and lower interface of the perovskite film without a buffer layer. This indicates that there is a large stress difference between the upper and lower surfaces of the annealed film, which may be caused by the mismatch in thermal expansion coefficients between the substrate and the perovskite layer ( Figure 4 a). However, the (100) crystal plane diffraction peak shift difference between the upper and lower surfaces of the perovskite film grown on the substrate with the added buffer layer is small, indicating that the residual stress in the film has been released ( Figure 4 b).

[0040] Reference Figure 5 In order to study the effect of introducing interface buffer on the quality of perovskite film, the buried interface of perovskite film was first explored using scanning electron microscopy (SEM). The buried interface was revealed by lower interface peeling. The results showed that the film flatness was poor at the buried interface without buffer layer, the grain growth was disordered, and there was obvious extrusion deformation at the grain boundary; this phenomenon may be due to the mismatch of thermal expansion coefficients between substrate and perovskite during annealing, which ultimately led to stress accumulation at the buried interface ( Figure 5 a). On the contrary, after adding the buffer layer, the flatness of the film and the contact between the buried interface grain boundaries are improved because the buffer layer relieves the stress accumulation ( Figure 5 b).

[0041] Reference Figure 6Scanning electron microscopy of the upper surface of the perovskite shows that the upper surface film lacking a buffer layer contains holes and has poor flatness. This may be due to the stress accumulation at the underlying interface, which leads to disordered grain growth, thereby exacerbating the stress accumulation at the upper surface film, resulting in the squeezing of the upper surface grains ( Figure 6 a). In addition, the introduction of the buffer layer significantly alleviates the extrusion deformation of the grains, indicating that the stress of the film on the upper surface is relaxed ( Figure 6 b).

[0042] Reference Figure 7 , using depth-resolved grazing incidence X-ray diffraction (GIXRD) technology. The GIXRD spectra corresponding to the (100) crystal plane at different ψ values ​​are shown in the figure below. Figure 7 As shown, Figure 7 a shows that the (100) plane distance increases with the increase of the diffraction angle. According to the Bragg equation nλ = 2dsinθ, the blue shift of the scattering peak indicates that the crystal plane distance increases, indicating that there is lattice tensile strain in the perovskite film. After adding the buffer layer, the (100) crystal plane diffraction peak of the perovskite film has only an almost invisible shift, indicating that the lattice tensile strain inside the plane is released ( Figure 7 b).

[0043] Reference Figure 8 The steady-state luminescence spectrum of the perovskite film at the buried interface is as follows: Figure 8 As shown in a, the perovskite film grown on the interface buffer layer substrate has the strongest PL absorption peak, indicating that the treatment with diphenylamine derivative molecules reduces the non-radiative recombination of the perovskite film. In addition, the average carrier lifetimes of the control group and the optimized group are 2553.8 ns and 3932.8 ns, respectively ( Figure 8 b) These results indicate that the introduction of diphenylamine derivative molecules into the buried interface of perovskite can effectively improve the film quality and reduce non-radiative recombination. The enhancement of PL intensity and the extension of carrier lifetime both indicate the reduction of trap state density.

[0044] Photovoltaic conversion efficiency test of battery device: At room temperature, using Keithley 2400 solar simulator, at a light intensity of 100 mW / cm 2 The cell efficiency test was carried out under (AM 1.5G) conditions. Through the cell device photoelectric conversion efficiency test, the photoelectric conversion efficiency of the prepared perovskite solar cell was 25.72%. Fig. 9 After adding the buffer layer, all parameters of the device are significantly improved, among which the filling improvement of the device is more obvious. This may be due to the release of the residual stress at the interface, which improves the film quality at the buried interface and promotes the orderly crystallization of the lower interface, and finally obtains a PCE of 25.72.

[0045] Example 2 Step 1, cleaning FTO glass substrate: select fluorine-doped SnO 2 (FTO) transparent conductive glass (2.5*2.5 cm 2 ), wipe off the impurities on the surface with dust-free paper, then use acetone, isopropanol, ethanol and ultrapure water for ultrasonic cleaning for 30 minutes each, blow dry, and treat with ultraviolet ozone for standby use; Step 2, preparing nickel oxide nanoparticle aqueous dispersion: Firstly, a nickel oxide nanoparticle aqueous dispersion is prepared and ultrasonically dispersed; After spin coating and annealing the aqueous dispersion of nickel oxide nanoparticles, a nickel oxide hole transport layer is obtained; Step 3, prepare SAM solution: First, prepare SAM dispersion and disperse by ultrasonication; After spin coating and annealing of the SAM dispersion, a SAM hole transport layer is obtained; Step 4: Prepare the interface buffer layer: After the annealed SAM substrate is cooled to room temperature, the buffer layer molecules are spin-coated or evaporated on the SAM substrate, followed by annealing.

[0046] Step 5, preparing a perovskite light absorption layer; Weigh PbI 2 :CH(NH 2 ) 2 I: Three solutes of CsI are dissolved in a DMSO / DMF mixed solvent; the mixed solution is sealed, stirred sufficiently, and filtered to obtain a clear perovskite solution for use; The perovskite precursor solution is uniformly coated on the surface of the interface buffer layer substrate; the perovskite wet film is obtained by spin coating and then placed on a hot plate at 100° C. for 20 minutes to obtain a perovskite light absorption layer; Step 6: Preparation of PCBM transport layer: The annealed perovskite film was cooled to room temperature, and the PCBM solution was spin-coated on the perovskite substrate to obtain the electron transport layer.

[0047] Step 7, preparation of BCP barrier layer.

[0048] The BCP solution was spin-coated on the surface of the PCBM layer or a 6 nm BCP layer was vacuum-evaporated on the surface of the PCBM.

[0049] Step 7, silver electrode evaporation: The prepared film was transferred into the evaporation chamber and 80 nm thick silver electrode was deposited by thermal evaporation. The effective area of ​​the mask was 0.09 cm 2 .

[0050] Reference Fig.10, Photovoltaic conversion efficiency test of battery device: At room temperature, using Keithley 2400 solar simulator, at a light intensity of 100 mW / cm 2 The cell efficiency test was carried out under (AM 1.5G) conditions, and the photoelectric conversion efficiency of the cell device was tested. The photoelectric conversion efficiency of the prepared perovskite solar cell was 25.43%.

[0051] Example 3 Step 1, cleaning FTO glass substrate: select fluorine-doped SnO 2 (FTO) transparent conductive glass (2.5*2.5 cm 2 ), wipe off the impurities on the surface with dust-free paper, then use acetone, isopropanol, ethanol and ultrapure water for ultrasonic cleaning for 30 minutes each, blow dry, and treat with ultraviolet ozone for standby use; Step 2, preparing nickel oxide nanoparticle aqueous dispersion: Firstly, a nickel oxide nanoparticle aqueous dispersion is prepared and ultrasonically dispersed; After spin coating and annealing the aqueous dispersion of nickel oxide nanoparticles, a nickel oxide hole transport layer is obtained; Step 3, prepare SAM solution: First, prepare SAM dispersion and disperse by ultrasonication; After spin coating and annealing of the SAM dispersion, a SAM hole transport layer is obtained; Step 4: Prepare the interface buffer layer: After the annealed SAM substrate is cooled to room temperature, the buffer layer molecules are spin-coated or evaporated on the SAM substrate, followed by annealing.

[0052] Step 5, preparing a perovskite light absorption layer; Weigh PbI 2 :CH(NH 2 ) 2 I: Three solutes of CsI are dissolved in a DMSO / DMF mixed solvent; the mixed solution is sealed, stirred sufficiently, and filtered to obtain a clear perovskite solution for use; The perovskite precursor solution is uniformly coated on the surface of the interface buffer layer substrate; the perovskite wet film is obtained by spin coating and then placed on a 120° C. hot plate for 15 minutes to obtain a perovskite light absorption layer; Step 6: Preparation of PCBM transport layer: The annealed perovskite film was cooled to room temperature, and the PCBM solution was spin-coated on the perovskite substrate to obtain the electron transport layer.

[0053] Step 7, preparation of BCP barrier layer.

[0054] The BCP solution was spin-coated on the surface of the PCBM layer or a 6 nm BCP layer was vacuum-evaporated on the surface of the PCBM.

[0055] Step 8, silver electrode evaporation: The prepared film was transferred into the evaporation chamber and a 90 nm thick silver electrode was deposited using thermal evaporation. The effective area of ​​the mask was 0.09 cm 2 .

[0056] Reference Fig.11 , Photovoltaic conversion efficiency test of battery device: At room temperature, using Keithley 2400 solar simulator, at a light intensity of 100 mW / cm 2 The cell efficiency test was carried out under (AM 1.5G) conditions, and the photoelectric conversion efficiency of the cell device was tested. The photoelectric conversion efficiency of the prepared perovskite solar cell was 25.29%.

[0057] The present invention also discloses a perovskite solar cell device prepared according to a method for preparing a high-efficiency inverted perovskite cell based on buried interface stress release, wherein the structure of the perovskite solar cell device is, from bottom to top, an FTO substrate, a NiO x Hole transport layer, SAM hole transport layer, interface buffer layer, perovskite absorption layer, PCBM electron transport layer, BCP blocking layer and silver electrode, among which the interface buffer (triphenylamine derivative molecule) is integrated into the buried interface of the perovskite layer. Due to its symmetrical molecular structure and unique active site (CN), it can bind to Pb 2+ The differential coordination of iodine significantly inhibits the formation of iodine vacancy defects, thereby effectively promoting the extraction and transfer of holes. In addition, due to its enhanced compatibility, the interfacial buffer can well regulate the energy level arrangement between the hole transport layer and the perovskite. In addition, the multiple rigid structures within the buffer molecules effectively constrain the expansion and contraction of the lattice while reducing the stress accumulation at the interface. Taking advantage of these advantages, we obtained low-stress, high-quality perovskite films, which are characterized by reduced charge transfer barriers and suppressed non-radiative recombination processes, ultimately resulting in more stable inverse perovskite cell devices, whose low cost, simple preparation process, excellent optoelectronic performance and device efficiency will help promote perovskite solar cells towards commercial applications.

[0058] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.

Claims

1. A method for preparing a high-efficiency inverse perovskite cell based on buried interface stress release, characterized in that: The following steps are involved: Step 1, cleaning the FTO glass substrate to obtain a pretreated FTO glass substrate; Step 2, spin coating a nickel oxide nanoparticle aqueous dispersion on the surface of the pretreated FTO glass substrate, and then performing a first annealing treatment to obtain a primary product having a nickel oxide hole transport layer; Step 3, dispersing the SAM powder into an isopropanol solution to prepare a SAM isopropanol mixed solution, and then spin-coating the SAM isopropanol mixed solution onto the surface of the nickel oxide hole transport layer of the primary product, and then performing a second annealing treatment to obtain a secondary product having a SAM hole transport layer; Step 4, spin coating the triphenylamine derivative molecular solution onto the surface of the SAM hole transport layer of the secondary product, and then performing a third annealing treatment to obtain a tertiary product with an interface buffer layer; Step 5, spin-coating the perovskite precursor solution onto the surface of the interface buffer layer of the tertiary product to obtain a quaternary product having a perovskite light absorption layer; Step 6, at room temperature, spin-coating a PCBM chlorobenzene solution on the perovskite film of the fourth product to form a fifth product having a PCBM electron transport layer; Step 7, preparing a BCP barrier layer on the PCBM electron transport layer of the fifth product to form a sixth product having a BCP barrier layer; Step 8, evaporating a silver electrode on the BCP barrier layer of the sixth product to obtain a perovskite battery device.

2. The method for preparing a high-efficiency inverse perovskite battery based on buried interface stress release according to claim 1, characterized in that: In step 1, the FTO glass substrate uses fluorine-doped SnO2 transparent conductive glass; when cleaning, the FTO glass substrate is ultrasonically cleaned using acetone solution, isopropanol solution, ethanol solution and ultrapure water in sequence, then blown dry, and finally subjected to ultraviolet ozone treatment to obtain a pretreated FTO glass substrate.

3. The method for preparing a high-efficiency inverse perovskite battery based on buried interface stress release according to claim 1, characterized in that: In step 2, the nickel oxide nanoparticles / water in the nickel oxide nanoparticles aqueous dispersion is 0.5-1 mg / mL, the spin coating speed is 3000r-5000r / 30s, and the spin coating thickness is 10-40nm; during the first annealing treatment, the temperature is 100-150°C and the time is 30-60min.

4. The method for preparing a high-efficiency inverse perovskite battery based on buried interface stress release according to claim 1, characterized in that: In step 3, the concentration of the SAM isopropanol mixed solution is 0.5-1.5 mg / mL, and the spin coating speed is 2000r~4000r / 30s; during the second annealing treatment, the temperature is 100~150°C and the time is 5~25min.

5. The method for preparing a high-efficiency inverse perovskite battery based on buried interface stress release according to claim 1, characterized in that: In step 4, the triphenylamine derivative molecular solution is prepared by dissolving the triphenylamine derivative molecular powder in a chlorobenzene solution to obtain a triphenylamine derivative molecular solution with a concentration of 0.5-1.5 mg / mL; wherein the structural formula of the triphenylamine derivative molecule is: During the third annealing treatment, the temperature is 100~150 ℃ and the time is 5~25min.

6. The method for preparing a high-efficiency inverse perovskite battery based on buried interface stress release according to claim 1, characterized in that: In step 5, the perovskite precursor solution is prepared by dissolving PbI2:CH(NH2)2I:CsI with a solute molar ratio of 1:0.98:0.02 in a mixed solvent of DMSO:DMF with a ratio of 1:4 to obtain a perovskite precursor solution; During spin coating, the volume of the added perovskite solution and the area of ​​the perovskite film are related to 9.6~11 μL / cm 2 ; The thickness of the perovskite light absorption layer is 700~800nm.

7. The method for preparing a high-efficiency inverse perovskite battery based on buried interface stress release according to claim 1, characterized in that: In step 6, during spin coating, the volume of the electron transport layer solution added is related to the area of ​​the perovskite film by 8-9.6 μL / cm 2 .

8. The method for preparing a high-efficiency inverse perovskite battery based on buried interface stress release according to claim 1, characterized in that: In step 7, the solvent of the BCP solution is isopropanol. When spin-coating, the thickness of the BCP barrier layer is 3-8 nm; when vacuum thermal evaporation is performed, the thickness of the BCP barrier layer is 5-15 nm.

9. The method for preparing a high-efficiency inverse perovskite battery based on buried interface stress release according to claim 1, characterized in that: In step 8, a silver electrode with a thickness of 80 to 100 nm is deposited by thermal evaporation.

10. A battery device obtained by the method for preparing a high-efficiency inverse perovskite battery based on buried interface stress release according to any one of claims 1 to 9, characterized in that: The battery device structure is FTO substrate, NiO x Hole transport layer, SAM hole transport layer, interface buffer layer, perovskite absorption layer, PCBM electron transport layer, BCP blocking layer and silver electrode.

Citation Information

Patent Citations

  • Merocyanine dye taking triphenylamine as donor as well as preparation method and application of merocyanine dye

    CN112876874A

  • Triphenylamine binaphthol copolymer and application thereof in solar cell

    CN114085361A

  • Inverted-structure perovskite solar cell based on benzodithienyl interface material and preparation method of inverted-structure perovskite solar cell

    CN118632549A

  • Organic thin film

    JP1992129271A

  • Organic electroluminescent diode and method for manufacturing hole transporting layer thereof

    US20180123041A1